The Coffee Bean simple Lesson to create positive change - Gordon, Jon. and Damon West (New Jersey Wiley and Sons, 2019)
Life is often difficult. It can be harsh, stressful, and feel like a pot of boiling hot water. The environments we find ourselves in can change, weaken, or harden us, and test who we truly are. We can be like the carrot that weakens in the pot or like the egg that hardens. Or, we can be like the coffee bean and discover the power inside us to transform our environment.
Keywords: Change